When capital meets control: governance dilemmas of financial investors in PPP projects - Chen, Chuan; Chen, Baoheng (Journal of Civil Engineering and Management, 2026)
While financial investors typically provide substantial share of capital in Public Private Partnership (PPP) Projects, they frequently lack meaningful operational control, leaving them vulnerable to opportunism from both government entities and contractors (i.e., industrial investors). This study investigates these unique governance challenges through a dual trajectory approach: first, by developing a comprehensive PPP governance theoretical model specifically tailored to financial investors’ needs, and second, by empirically validating this model through an in-depth case analysis of a financial investor’s innovative governance practices. The research makes three significant contributions to the field: First, it reconceptualizes financial investors as distinct stakeholders with specialized governance requirements in PPP ecosystems. Second, it advances a holistic theoretical model comprising 19 critical governance elements across institutional, organizational, contractual, and managerial dimensions. Third, it derives four practical, evidence-based strategies for maintaining control while preserving partnership viability: 1) implementing contractor profit-sharing mechanisms to align incentives, 2) developing integrated risk-transfer structures, 3) establishing joint government-contractor oversight systems, and 4) creating debt service reserve funds from construction margins to mitigate government payment delays. These findings offer both theoretical insights and actionable solutions for improving financial investor protection in PPP arrangements.